PENETAPAN BOBOT TIMBULAN SAMPAH RUMAH TANGGA DI TIGA LINGKUNGAN DI KELURAHAN BANTAN KECAMATAN MEDAN TEMBUNG KOTA MEDAN - Zakki Rizkiyah; Meida Nugrahalia; Rosliana Lubis (BIOLINK (Jurnal Biologi Lingkungan Industri Kesehatan), 2017)
This reseach aims was to find out how much of the total solid waste generated both organic and inorganic solid waste weight calculation is done in the village Batan. This type of research is descriptive research with sampling propotional stratified random sampling method. From the data obtained is then perfomed calculation of average waste generation per capita per day, and presentage of the composation. Result of the study found that the average weight of waste generation on the Linkungan IX 0,30 Kg/soul/day, Lingkungan XI 0,37 Kg/soul/day and the Lingkungan XII 0,343 Kg/soul/day. The perecentage compotition of the organic waste of the Lingkungan IX at 57% and 43% inorganic waste, Lingkungan XI 54% organic and 40% for inorganic waste and Lingkungan XII where as 54% of organic waste inrganic 46%. Average weigth of waste to high-income households 1,03 Kg/soul/day, was 0,99 Kg/soul/day and allow 1:03 Kg/soul/day. The perecentage weigth of waste product by high-income households the Lingkungan IX, XI, XII respect tively 32%, 37%, 31%. Modereta income households in the Lingkungan IX, XI, XII respect tively 33%, 35%, 34%. Are for low-income households in the Lingkungan IX 31%,35% Lingkungan XI and XII 34%.